Global trends of secondhand smoke exposure among young adolescents from 27 countries, 2003–2021: findings from the World Health Organization database - Sooji Lee; Yejun Son; Seohyun Hong; Myeongcheol Lee; Hyejun Kim; Hojae Lee; Hayeon Lee; Hyeri Lee; Jaeyu Park; Elena Dragioti; Guillaume Fond; Laurent Boyer; et al. (Scientific Reports)
Abstract The issue of adolescent secondhand smoke (SHS) is globally significant, given that it serves as a preventable risk factor for disease prevalence and mortality rates among youth. This study evaluates trends in adolescent SHS across 27 countries from 2003 to 2021, aiming to identify global variations and sex-specific differences, providing insights for future policy recommendations. The data for this study were collected from the Global School-based Student Health Survey conducted by the World Health Organization, 2003–2021. The term SHS in this context denoted how many days people smoked in their presence for at least one day within the past 7 days. Linear regression models were employed to examine the trends of SHS exposure by country. In the present analysis based on 175,370 adolescents (male, 46.69%) aged between 13 and 15 years from 27 countries across the five continents, SHS decreased in 14 countries but exhibited an increasing trend in 3 countries (Benin [β, 3.20; 95% CI, 2.50–3.91]; Maldives [β, 0.93; 0.21–1.65]; Myanmar [β, 0.62; 0.29–0.95]). Significant increasing trends in females were observed in the Maldives (β, 1.18; 0.25–2.11) and Thailand (β, 0.36; 0.04–0.69) while males showed increasing trends in Kuwait (β, 1.90; 0.79-3.00) and Vanuatu (β, 1.95; 0.35–3.54). Our analysis of adolescents from 27 countries indicates that the majority of nations exhibited decreasing trends in SHS. This suggests that global efforts to prevent SHS are achievable through individual initiatives and international monitoring. However, the presence of increasing trends in certain countries underscores the need for stronger regulations and policies to address this issue.